Rebalancing China's Economy: Domestic and International Implications. Issue 1 (January 2017) - Ma, Guonan; Roberts, Ivan; Kelly, Gerard
Abstract: This paper considers interactions between China's domestic and external imbalances and their global implications. We present scenarios detailing how a rebalancing of China's growth pattern from investment‐driven growth towards more consumption‐driven growth may occur in practice. Using input–output tables for 2012, we illustrate the knife‐edged nature of Chinese rebalancing, the linkages between expenditure‐side and production‐side rebalancing, and how an internal rebalancing could exacerbate external imbalances. A policy implication for China is that for rebalancing to be fast, consumption must be exceptionally resilient and the efficiency of investment must increase sharply. If rebalancing is too slow, the capital‐to‐output ratio will rise to potentially unsustainable levels and consumption will fail to attain levels of contemporary upper middle‐income economies by 2030. Global input–output tables (1995–2011) suggest that the patterns of Chinese rebalancing considered in our scenarios may generate substantial headwinds for exports to China by its trading partners.